Surrender your market! Do the G5 countries use World Bank Trade Conditionality to promote Trade? - Martin Breßlein; Maya Schmaljohann (University of Heidelberg, Department of Economics, 2013)
In this paper we investigate whether the design of World Bank conditionality, namely the extent of trade liberalization conditions, is influenced by the commercial motives of the Bank's five major shareholders. Using a newly available dataset on World Bank conditionality we analyze the conditionality design of more than 870 projects over the 1981 – 2010 period. Our results suggest that countries of commercial interest for Germany have, on average, more trade liberalization conditions attached to their loans, indicating a trade promotion strategy. For the US, on the other hand, our results show that trading partners receive significantly fewer trade conditions. This suggests protection of the own bilateral trading relations from competition that would arise in the case of more open markets.
urn:nbn:de:bsz:16-heidok-155121
Keywords: 330; Foreign trade; lending; World Bank conditionality